Face mask exemptions, psychiatric patients, and COVID-19 - Ayuso-Mateos, José Luis (Eur Psychiatry, 2020)
It has been compulsory to wear face masks in all public spaces, both indoor and outdoor, since May 21, 2020 throughout Spain [1], a measure intended to prevent the spread of coronavirus disease 2019 (COVID-19). However, there are some exceptions to this rule, including “… People for whom the use of a mask is inadvisable for duly justified health reasons, or who, due to their disability or dependency, present behavioural alterations that make its use unviable.”